The kids' encyclopedia of things to make and do - Rasmussen, Richard Michael (Minnesota : Toys 'n Things Press, 1988)
Instructions for over 1800 art and craft projects which are listed in alphabetical order by subject.
Keywords: Creative activities ans seat work -- Juvenile literature; Handicraft -- Juvenile literature